Effects of water quality on waterbird diversity in converted oil palm plantations - Sulai, Petra (2017)
Oil palm extension is a major driver for habitat loss in the tropics. Yet, while a number of studies have focussed on the consequences for terrestrial biodiversity, the impacts on waterbirds habitats and their associated fauna are less well described. Little information is available to guide the management of waterbirds and their habitat in oil palm production landscapes, particularly on those converted from natural wetlands such as mangrove and peat swamp forests. This study aims to determine the conservation value of flood-control drainage channels for waterbirds in oil palm plantations. This study also measured the water quality indicators (water temperature, pH, dissolved oxygen (DO), total dissolved solids (TDS), salinity, water depth, conductivity, turbidity) and habitat characteristics (vegetation cover and channel width)to determine the relationships between waterbird species richness, water quality and habitat characteristics. Birds were surveyed along twenty five line transects within the peat swamp-converted and mangroves-converted oil palm smallholdings. Water quality parameter was measured in the middle of each line transects. Data was collected in seven smallholdings between March and December 2013. This study was recorded a total of 1111 waterbirds from eight resident species. Both mangrove forest-converted smallholdings and peat swamp-converted smallholdings had similar waterbirds diversity. Waterbirds species richness increased with increasing DO and decreased with water depth, temperature and conductivity. This association may be because of the suitability of the flood-control channels for aquatic invertebrates and fish, both of which are consumed by waterbirds and depend on sufficient levels of DO in the water to survive. The most parsimonious predictive model (minimum AIC = 476.48) explained 52.39% of the variation in the species richness. The data suggest that even man-made aquatic habitats, such as flood control channels, can be important for some conserving waterbirds in oil palm smallholdings. However, given the relatively small gains in terms of increased waterbird species richness in channels, the most successful strategy for conserving waterbirds still require the protection of intact wetlands that supported by better management of drainage channels in oil palm smallholdings.